THE SEMIOTICS ANALYSIS ON THE ENVIRONMENT IN â€œTHE JOURNEY TO ATLANTISâ€ PICTURE BOOK - Suparno, Darsita; Kusumoriny, Laksmy Ady (Universitas Pamulang, 2020)
This study aimed (1) to describe the semiotic process of environment symbols in The Journey to Atlantis, (2)to generate the meaning of identified symbols which are shown through verbal and non-verbal contained in The Journey to Atlantis. This study uses a descriptive qualitative method which tries to identify, analyze semiosis process of environment symbols, and describe the found verbal and nonverbal symbols in Elisabetta Dami?s The Journey to Atlantis Picture Book using semiotic theory by Charles Sanders Peirce (1991). The data for the finding and analysis were taken from Elisabetta Dami?sThe Journey to Atlantis (2012) Picture Book. The result of this study shows 40 icon in form of words and 36 onomatopoeia as verbal symbols, and 40 picture decribe Atlantis environment and 18 color as nonverbal symbols which are related to the environment.